2021
DOI: 10.1002/cctc.202101220
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Apatite Supported Molybdenum Oxide Catalysts for Selective Oxidation of Methanol to Formaldehyde: Structure, Activity and Stability

Abstract: Molybdenum oxide (5 to 20 wt.%) supported on calcium or strontium hydroxyapatite were investigated as catalysts for selective oxidation of methanol to formaldehyde. These catalysts were both active and selective, with a maximum yield achieved at 95 % conversion and 96 % selectivity. The main byproducts were CO (3.2 %) and dimethyl ether (DME, 0.7 %). The catalytic performance of the catalysts was measured for up to 600 h at 350 °C. Compared to an industrial iron molybdate catalyst, the hydroxyapatite based cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…Others have suggested that there could be better catalysts. For instance, Thrane et al [35] consider that apatite may be a more stable and active support medium for molybdenum oxide, and Bowker et al [36] report that higher area, more active materials may be produced by Al doping in the bulk of the catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that there could be better catalysts. For instance, Thrane et al [35] consider that apatite may be a more stable and active support medium for molybdenum oxide, and Bowker et al [36] report that higher area, more active materials may be produced by Al doping in the bulk of the catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, no catalyst that has the potential to fully exchange the FeMo catalyst in the industrial (Formox) process has been reported. However, some catalysts showed higher stability/lower molybdenum loss and similar activity and reasonable, but slightly lower, selectivity compared to the FeMo catalyst, including a recently developed MoO 3 /HAP catalyst [110,112]. Such catalysts could possibly be used in the inlet section of the reactor, providing moderate conversion over this alternative catalyst, where selectivity is rather high.…”
Section: Discussionmentioning
confidence: 99%
“…However, no Mo volatilization past the point of stoichiometry for the bulk alkali earth metal molybdates was observed by Raman spectroscopy [107]. However, in the later study of MoO 3 supported on HAP and the Sr analogue, Thrane et al [110] found that the amount of CaMoO 4 and SrMoO 4 quantified by XRD decreased with TOS for samples with nominal loadings of 10 and 15 wt% MoO 3 . Thus, CaMoO 4 loading went from 8.1 to 3.1 wt% after 408 h on stream for the 10 wt% MoO 3 /HAP.…”
Section: Volatility Of the Active Phasementioning
confidence: 96%
See 2 more Smart Citations